Solicitation of Public and Private Litigation Under the First Amendment - Donald P. Simet (Washington University Law Quarterly, 1978)
After presenting the solicitation cases, the Article will analyze the nearest precedents bearing on each.
Keywords: Attorneys; Freedom of speech; Legal ethics